Through Others We Become Ourselves: How Service-learning Develops Graduate Identity - Alison Walker (SAGE Handbook of Graduate Employability, 2022)
In this chapter we introduce a ‘Quadruple Helix’ to illustrate the development of graduate identity through service-learning (SL). This approach is an adaptation of Chickering and Braskamp's (2009) four vectors of psychosocial development, onto which we have mapped findings from our research with psychology undergraduates who completed an SL module. It offers a framework to understand the processes through which SL can facilitate identity development and provides a model for creating a more holistic approach to embedding employability and graduate attributes in HE.